O direito fundamental à igualdade e a ordem de julgamento dos processos judiciais - Teixeira, Bruno Buback (2011)
Actually, the declaration and guarantee of fundamentals rights are requirements to formulation of the Constitutional State of Law. The Jurisdiction, as a function of the State and the citizens guarantees, provides accomplish of the fundamentals rights in the situations where the rights were violated and the promotion those it never were achieved before. The time factor is determinant to effective guarantee of fundamentals rights accomplishing of jurisdictional activities through judicial process of conflict resolution. In this context, it‟s originated the fundamentals guarantees of the reasonable process duration. It should attend time requirements beyond protect others fundamentals rights. Specially, the equality right is inherent to own determination of a reasonable duration considering that the citizens in equals situations have rights in the same criterion of reasonable as to process duration avoiding preferences or undue delay. Therefore, the process choice order waiting practice of the same act will consider the process time as a determinant factor to celerity or retardation of the act achieving, in favor of reasonable process duration, privileging same over others and pondering the fundamental rights to equality. Of this way, the problem consists to answer this question: What the impact of process order achieving the procedural acts on fundamental right to equality? The established goals are: to determine the sense of fundamental right to equality; to identify the relationship among isonomy, time factor and reasonable process duration guarantee; to determine the sense of reasonable process duration guarantee; and, finally, to establish a way of sort the process to practice of the judicial acts considering the fundamentals rights to equality without abandonment of reasonable process duration. Regarding the first goals, the method was the deductive and the bibliography research sought develop theoretically the rights to equality and to guarantee of reasonable process duration. For the final goal was used a transdisciplinary research to discover a way of process ordering involving the equality and the reasonable duration of process to study the sequence rules in the discipline of Planning and Control of Production in the Production Engineering Course of Exact Science. In summary, its correlates several factors (like priorities, due date, process time, restrictions, and else) to obtain certain goals specifying the appropriate sequence. Thus, perceives that the choice order of process to practice the procedurals acts may violate the equality in formal or material sense. Also, it‟s not possible to think only in the fundamental right to equality in the formulation of the process order at the risk of harm in the guarantee of reasonable process duration. In conclusion of this research, tried to educate a way to think a process ordering first based on the fundamental rights to equality and, then, based on in the guarantee of reasonable process duration.